Szkolnictwo wyższe wobec potrzeb rynku pracy = Higher education vs the needs of the labour market - Radziewicz-Winnicki, Andrzej; Wołk, Zdzisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Higher education in the post-industrial world is striving with the task to prepare young people to undertake professional activity. It plays an important role as a factor conditioning the prosperity of professional careers. As higher education has became more and more widespread, there appeared problems connected with the profusion of well-educated people in the labour market which results in the increased number of unemployed people who completed higher education especially the secondcycle studies or the doctoral studies.
Keywords: szkolnictwo wyższe; rynek pracy; absolwenci